Overexpression of Kcnmb2 in Dorsal CA1 of Offspring Mice Rescues Hippocampal Dysfunction Caused by a Methyl Donor-Rich Paternal Diet - Yu, Ming; Guo, Li; Li, Nan; Henzel, Kristin S.; Gu, Huating; Ran, Xiufang; Sun, Wei; Liu, Shuai; Lu, Yingchang; Ehninger, Dan; Zhou, Yu (Frontiers in Cellular Neuroscience, 2018)
BK channels are known regulators of neuronal excitability, synaptic plasticity and memory. Our previous study showed that a paternal methyl donor-rich diet reduced the expression of Kcnmb2, which encodes BK channel subunit beta 2, and caused memory deficits in offspring mice. To explore the underlying cellular mechanisms, we investigated the intrinsic and synaptic properties of CA1 pyramidal neurons of the F1 offspring mice whose fathers were fed with either a methyl donor-rich diet (MD) or regular control diet (CD) for 6 weeks before mating. Whole-cell patch-clamp recordings of CA1 pyramidal neurons revealed a decrease in intrinsic excitability and reduced frequency of inhibitory postsynaptic currents (IPSCs) in MD F1 mice compared to the CD F1 controls. AAV-based overexpression of Kcnmb2 in dorsal CA1 ameliorated changes in neuronal excitability, synaptic transmission and plasticity in MD F1 mice. Our findings thus indicate that a transient paternal exposure to a methyl donor-rich diet prior to mating alters Kcnmb2-sensitive hippocampal functions in offspring animals.